2003
DOI: 10.1073/pnas.0434312100
|View full text |Cite
|
Sign up to set email alerts
|

Rnf2 ( Ring1b ) deficiency causes gastrulation arrest and cell cycle inhibition

Abstract: The highly homologous Rnf2 (Ring1b) and Ring1 (Ring1a) proteins were identified as in vivo interactors of the Polycomb Group (PcG) protein Bmi1. Functional ablation of Rnf2 results in gastrulation arrest, in contrast to relatively mild phenotypes in most other PcG gene null mutants belonging to the same functional group, among which is Ring1. Developmental defects occur in both embryonic and extraembryonic tissues during gastrulation. The early lethal phenotype is reminiscent of that of the PcG-gene knockouts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
265
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(274 citation statements)
references
References 60 publications
4
265
1
1
Order By: Relevance
“…RNF2 is recruited to the E2F1-binding promoters and plays a role in the prohibitin-mediated repression of E2F1 transcriptional activity It was previously reported that the p16 expression level was increased in RNF2-knockout mice (Voncken et al, 2003). We also found that RNF2 interacted with prohibitin.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…RNF2 is recruited to the E2F1-binding promoters and plays a role in the prohibitin-mediated repression of E2F1 transcriptional activity It was previously reported that the p16 expression level was increased in RNF2-knockout mice (Voncken et al, 2003). We also found that RNF2 interacted with prohibitin.…”
Section: Resultsmentioning
confidence: 51%
“…Protein levels of p16 are increased by prohibitin or RNF2 depletion In the previous report, the expression of p16 INK4a was found to be upregulated in RNF2-knockout mice (Voncken et al, 2003). We tested whether the protein expression level of endogenous p16 is affected by the overexpression or knockdown of RNF2 in HEK293 cells ( Figure 4a).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Histone H2A monoubiquitylation depends critically on Ring1B/Rnf2; this may explain the embryonic lethality observed in constitutive loss-of-function Ring1B/Rnf2 knock-out mice (23). Correlative evidence shows that this histone modification is associated with transcriptional repression; however, the molecular basis (for instance cross-talk between histone modifications) underlying this function is not known.…”
mentioning
confidence: 95%
“…For example, mice transgenic for Bmi1, Mel18 and M33 genes show hematopoietic anomalies such as severe spleen and thymus hypoplasia, [17][18][19] and Rnf2 deficiency results in an early lethal phenotype. 20 Studies of PcG in human tissues show that this system plays important roles in several biological functions, such as regulation of cell differentiation, 16,18,21,22 hematopoietic and neural stem cell self-renewal [23][24][25] and control of cellular proliferation. 3,17,18,21,[26][27][28][29] The role of PcG in human cancer is mostly unknown, but some evidence indicates the involvement of this system in tumorigenesis.…”
mentioning
confidence: 99%